Tropoelastin Implants That Accelerate Wound Repair. Issue 10 (16th February 2018) - Mithieux, Suzanne M.; Aghaei‐Ghareh‐Bolagh, Behnaz; Yan, Leping; Kuppan, Kekini V.; Wang, Yiwei; Garces‐Suarez, Francia; Li, Zhe; Maitz, Peter K.; Carter, Elizabeth A.; Limantoro, Christina; Chrzanowski, Wojciech; Cookson, David; et al.
Abstract: A novel, pure, synthetic material is presented that promotes the repair of full‐thickness skin wounds. The active component is tropoelastin and leverages its ability to promote new blood vessel formation and its cell recruiting properties to accelerate wound repair. Key to the technology is the use of a novel heat‐based, stabilized form of human tropoelastin which allows for tunable resorption. This implantable material contributes a tailored insert that can be shaped to the wound bed, where it hydrates to form a conformable protein hydrogel. Significant benefits in the extent of wound healing, dermal repair, and regeneration of mature epithelium in healthy pigs are demonstrated. The implant is compatible with initial co‐treatment with full‐ and split‐thickness skin grafts. The implant's superiority to sterile bandaging, commercial hydrogel and dermal regeneration template products is shown. On this basis, a new concept for a prefabricated tissue repair material for point‐of‐care treatment of open wounds is provided. Abstract : Heat‐stabilized tropoelastin provides a novel scalable approach to production of elastic materials. This is attractive because no chemicals are used to generate these elastic structures. The resulting heat‐treated tropoelastin promotes the repair of full‐thickness wounds.